Recht und Religion in Europa zeitgenössische Konflikte und historische Perspektiven - Langenfeld, Christine; Schneider, Irene (Universitätsverlag Göttingen, 2008)
What correlations exist between law and religion? To trace this relationship in selected periods and regions (the old East / Ancient, modern Europe, Islamic world) is the goal of this volume. As a specific thematic reference point, the editors have selected those tense relationship that exists between the law as a divine constitution and the law as a human right. The current occasion to address this matter was the perception of a resurgence of traditional religion, especially Islam.